Modelling invasion potential of Bighead Carp under climate change: effects of seasonal temperatures on a recruitment bottleneck - Erik K. Dean; D. Andrew R. Drake; Nicholas E. Mandrak (Biological Invasions, 2026)
Because young-of-year (YOY; age-0) are vulnerable to overwinter mortality, fishes invading higher latitudes could encounter colder conditions that impose population bottlenecks, but warming under climate change could reduce such restrictions. To examine how populations might respond to anticipated warming and whether they could establish, we developed a life-history model, integrating four published empirical relationships (daily YOY growth, length-energy relationships, length- and temperature-dependent energy loss, and length-dependent energy thresholds for mortality), to estimate YOY performance of invasive Bighead Carp ( Hypophthalmichthys nobilis ) in tributaries of the Laurentian Great Lakes under baseline, mid-century, and end-of-century climatic conditions. Based on daily temperatures, the model projected dates when spawning could occur, fish length and energy reserves acquired by the start of winter, and the amount of energy required to overwinter successfully. We determined that warming will increase YOY performance, overwinter survival, and the difficulty of managing a potential invasion due to increased growth, shorter periods of overwinter starvation, and longer periods of potential spawning activity. Advanced onset of spawn (e.g. up to 54 and 74 days earlier in the Nipigon River, by mid- and late-century) was the primary determinant of increased winter survival as early spawned fish had more opportunity to grow and acquire the energy necessary to endure overwinter starvation. As larger portions of each year become suitable for spawning, timelines for management will become less concentrated and control could be required for periods up to 2.5 times longer than baseline by end of century (from 67 to 164 harvest-days in the Genesee River). To optimize preventative measures against potential Bighead Carp invasions, we recommend focusing efforts on mitigating spawning in earlier months when YOY are most expected to survive winter, and to prioritize locations projected to have earlier spawning activity.

The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Genome analysis of gyroviruses identified in waterfowl in Arizona (USA) - Shawnpreet Sahnan; Diego Olivo; Joy M. Custer; Rohan A. Bandoo; Danny Jackson; Michael C. Lund; Hannah McGraw; Melanie Regney; Victor Aguiar de Souza Penha; Julia Neil; Dean Drake; Kevin McGraw; et al. (Archives of Virology, 2024)

Non-linear effects on the population performance of Bighead Carp under different maturation schedules - Erik K. Dean; D. Andrew R. Drake; Nicholas E. Mandrak (Biological Invasions, 2023)
Bighead Carp currently threatens to invade the Laurentian Great Lakes from the Mississippi River, but the novel climatic conditions it will encounter by expanding northwards could affect its population performance. Bighead Carp in colder climates exhibits slower growth and matures later, with later maturation typically leading to larger adult size and increased fecundity and survival. Accordingly, the life-history strategies of Bighead Carp at its northern range limits could differ from those observed in its current invaded range. To explore how population performance could differ across changing environmental conditions, we used a stage- and age-based matrix population model parameterized with values reported for Bighead Carp populations around the world. The model was used to evaluate how different ages of maturity and their resulting impacts to body size, survival, and fecundity could impact rates of population growth and establishment. Age of maturity had a non-linear effect on population growth, with maturation at intermediate ages (4–6 years) resulting in better performance. However, performance differed less between maturation ages when fecundity was allowed to increase disproportionately with body size. Greater population growth at younger ages of maturity suggest that invasion at lower latitudes could enable establishment in fewer years due to faster rates of development in warmer temperatures. Across all maturation schedules, population growth was most sensitive to the recruitment of age-1 individuals and least sensitive to adult survival, and vital rates overall varied more in their contribution to population growth at younger ages of maturity. Thus, understanding the factors that control age-1 recruitment would inform projections of population performance for Bighead Carp in the Laurentian Great Lakes.

Variation in plasma protein levels in House Finches (Haemorhous mexicanus): effects of season, disease state, and urbanization - Dean J. Drake; Kevin J. McGraw (Journal of Ornithology, 2023)